Logistics distribution optimization model using multi-depot capacitated vehicle routing problem - Rajagukguk, Angie Maretha; Esther Sorta Mauli Nababan; Parapat Gultom (Universitas Islam Negeri Raden Intan Lampung, 2025)
Logistics distribution is vital for enhancing the efficiency and competitiveness of Indonesia. This research focuses on logistics distribution by introducing temporary depots in strategic locations to address the growing demands of the rapidly expanding e-commerce and transportation industries. As consumers increasingly expect faster and more efficient deliveries, logistics systems must adapt with flexible solutions. Temporary depots offer a practical approach to reducing delivery time, optimizing vehicle routes, and improving service efficiency to meet modern distribution challenges. The Multi Depot Vehicle Routing Problem model developed focuses on optimizing depot locations, vehicle allocation, and delivery routes while minimizing total distribution costs, including shipping, vehicle usage, depot construction, and travel from the distribution center to temporary depots. This research addresses how to minimize operational distribution costs, considering logistical demand, vehicle capacity, region visits, and flow conservation, while adhering to non-negative and binary constraints. The model aims to contribute to more efficient logistics planning, operational cost savings, and enhanced supply chain sustainability in Indonesia.